Makna Tradisi Saparan di Desa Cukilan Kecamatan Suruh Kabupaten Semarang - Ida Zahara Adibah (Sekolah Tinggi Ilmu Tarbiyah (STIT) Pemalang, 2015)
Tradition is anything that is hereditary, which occurs over the interaction between one clan with another clan which then makes the habits of each other contained in the clan and then blend into one habit. This paper reveals the meanings of cultural symbols contained in the Saparan tradition in Cukilan Village, Suruh District, Semarang Regency. The values contained need to be revealed to get meaning that may have relevance to the interests of a particular person or group in general. Field research was conducted to reconstruct and analyze the traditions of the Javanese Islamic community in the form of the Saparan tradition. To obtain objective results, the method used is the historical approach, phenomenology, and ethnography.